Володимир Амвросійович Менчиць (1837-1916): історіографічний огляд напередодні сотих роковин з дня смерті - Гордійчук, Мирон Григорович (НТУ "ХПІ", 2015)
У статті наведено історіографічний огляд діяльності В. Менчиця (1837-1916) - видатного етнографа, власника мережі книгарень, де поширювалася зокрема і українофільська література, члена Петербурзької, Київської та Єлисаветградської громад. Його постать є цікавою для дослідників, зокрема й через його родинні зв’язки із М. Грушевським. Проаналізовано фактори недостатньої уваги дослідників до колоритної постаті В. Менчиця. На жаль, його постать і надалі залишається поза увагою дослідників громадівського руху і потребує актуалізації як цікавий і непересічний приклад життєвого шляху українофіла в ХІХ столітті.

The article presents historiographic review of the activity of Volodymyr Menchyts (1837-1916) – an outstanding ethnographer, the owner of bookshop chain which spread in particular the Ukrainophile literature, the member of the Southwestern Branch of the Imperial Russian Geographical Society, the participant of Petersburg, Kyiv and Yelysavethrad hromadas. V. Menchyts is significant for scientists especially because of his kindred relationship with Mykhailo Hrushevsky (he was Mykhailo Hrushevsky's uncle on his mother's side). We analyse factors of absence of scientists' proper attention to racy figure of V. Menchyts that de-serves the well-grounded monographic research. We present the periods of the study of Volodymyr Menchyts' figure: 1920-1930's, the next Soviet period and mentioning in modern Ukrainian historiography. This work is devoted to 100 anniversary of V. Menchyts' death.
Volodymyr Menchyts (1837-1936): historiographic review before the 100th death anniversary
Keywords: громадівський рух; етнографія; українофіли; Грушевський М.; hromada movement; ethnography